Outcomes of jejunostomy-tube placement in surgical patients with esophageal cancerCentral MessagePerspective - Hope Conrad, MD; Ahmed Elkamel, MBBS; Anthony Maltagliati, MD; Kevin Wang, MD; Chiu-Hsieh Hsu, PhD; Wendy Linville, BA; Michal Lada, MD; Praveen Sridhar, MD; Stephanie Worrell, MD (JTCVS Open)
Objective: Patients with esophageal cancer who undergo esophagectomy are at high risk for malnutrition. Jejunostomy tubes are often placed to provide enteral access for nutritional support. Traditionally, jejunostomy placement occurs at the time of esophagectomy. However, benefits have been described in patients with earlier jejunostomy placement. The purpose of this study is to determine outcomes of surgical patients with esophageal cancer on the basis of jejunostomy tube placement as well as to analyze the effect of placement timing on these factors. Methods: This is a retrospective, multi-institutional study including 2 academic hospital systems. Patients with esophageal cancer who underwent esophagectomy were included. Patients who received a jejunostomy tube were compared with patients who did not receive a jejunostomy tube. Further analysis comparing early and routine jejunostomy placement timing was then performed. Results: Of 327 included patients, 48.32% (158) had a jejunostomy tube and 51.68% (169) did not have any form of enteral access. For every day a patient had a jejunostomy tube in place, there was a reduction in hospital length of stay (LOS) and intensive care unit LOS (P ≤ .001 and < .001). Conclusions: Jejunostomy tube placement in patients with esophageal cancer undergoing esophagectomy significantly enhances nutritional outcomes, particularly in malnourished patients, and reduces 90-day mortality and recurrence rates. Patients with esophageal cancer who underwent esophagectomy and received an early jejunostomy tube had shorter hospital and intensive care unit LOS. Early placement of jejunostomy tubes should be considered to optimize nutritional support and improve overall patient resilience before surgery. Further prospective studies are warranted to confirm these findings and refine guidelines for jejunostomy tube placement in patients with esophageal cancer.